The relationships between self leadership and critical thinking - Semerci, Nuriye (Academic Journals, 2010)
The aim of this research is to address general relationships between self leadership and critical thinking as well as relationships with the sub dimensions Survey method was used in the research The population included 450 students in Firat University (of Turkey) attending pedagogical formation program for being teachers in secondary schools The study sample comprised of 386 students selected among those students on a random basis The proportion of the study sample to the population is 85 78% Two scales were applied to the students at the same time One of them is self leadership scale The other scale used in the study is the critical thinking scale Of the 386 students participating in the study, 221 are males (57 3%) and 165 are female (42 7%) There is a correlation of 0 41 between critical thinking and self leadership According to the results of multiple regression analysis held between sub dimensions of self leadership and critical thinking, regression equality regarding prediction of critical thinking (mathematical model) is as follows Critical thinking = 2 856 - 0 030 natural prize strategies - 0 337 behavior-oriented strategies - 0 231 constructive thinking model strategies + 0 957 general self leadership
Keywords: Self leadership; critical thinking; student